Public Perceptions about the P4K Program: A Qualitative Analysis Based on Theory of Planned Behavior - Tasiah Tasiah; Novita Novita (Global Health Science Group, 2023)
In improving the quality of maternal and child health services and preventing maternal deaths, community roles are needed, one of which is carried out through the implementation of the Childbirth Planning and Prevention of Complications (P4K) Program. However, there are still many pregnant women who eventually give birth in a shamans (dukun beranak or paraji)even though they have been affixed with a P4K sticker. Based on this phenomenon, this qualitative research was made with the aim of exploring people's perceptions of P4K and the reasons they still give birth in shamans using a grand theory, namely the theory of planned behavior. This research is qualitative research. The research was conducted in the working area of the Lebak Wangi Health Center in Serang City from May to June 2023. This qualitative research uses a grand theory in the form of a theory of planned behavior. The sample or respondents of this study were mothers who had P4K stickers at home but gave birth in paraji shamans as many as 5 people and 2 triangulators in this study were midwives. Data was collected by in-depth interviews. The analysis will be presented qualitatively with validity using peer triangulators. The informant's behavioral belief was that if the birth in a quack would be normal whereas if in a midwife there was a possibility of surgery or being referred to a hospital and patients were afraid so they ignored information related to P4K. Subjective norms are formed because of believing in shamans or their parents, having family ties or misinformation regarding preparation for childbirth, especially all information for P4K. In this study, the strongest reason related to control belief was the experience of having given birth normally without having to prepare what was mentioned in P4K.